Formar a los ciudadanos de la "República Católica" : la moral como base del proyecto educativo conservador (1842-1850) (2019)
This investigation analyzes the role that morality had in the process of construction and configuration of a "conservative" republican order between 1842 and 1850 in New Granada through its educational project. The objective of this work is to reconstruct the expectations of a group of intellectuals about the role of education in the formation of a desired type of Republic, as well as citizenship in the mid-nineteenth century guided by principles of Catholicism. I try, then, to understand the challenges that these intellectuals faced in an uncertain time, that is, in a time of both expectation and uncertainty, hope and mistrust, typical of the republican formation.